Ricoeur: from the phenomenology to the hermeneutics of the emotions - Cárdenas Mejía, Luz Gloria (Estudios de Filosofía, 2011)
This paper belongs to a research project on how Human Experience of Place has as starting point Aristotle’s observation of a fact: Passions present themselves together with judgment on a concrete and determined action. My intention is to collect the studies on Passions, Emotions and Feelings that are to be found in Ricoeur’s early production. I consider Ricoeur, firstly, because the question of the Human Establishment of Place, can be said, belongs to the domain of Phenomenology and Hermeneutics. Secondly, because the author makes use of the above terms and proposes to distinguish them, and this wil allow us to set up a framework for their uses.